The Effect of Diabetes Mellitus Exercises and Neuromuscular Taping (NMT) on Ankle Brachial Index (ABI) in Type 2 Dm Patients - Ulkhasanah, Muzaroah Ermawati; Widiastuti, Agung (Indonesian Journal of Global Health Research, 2024)
Diabetes mellitus is caused by metabolic disorders characterized by increased blood glucose levels due to insulin secretion. Complications of peripheral arterial DM cause decreased blood flow to the lower extremities, marked by a decrease in ABI. Non-pharmacological therapy requires diabetes exercises and NMT to prevent injury to the feet due to changes in peripheral blood circulation. Objective: research to determine the effect of diabetic foot exercises and NMT on ABI in Type 2 DM patients. Method: Quantitative design, quasi-experimental method, pre-test post-test control group design, sampling technique using purposive sampling. Observations assessed the ABI score before the diabetes exercise intervention in intervention 1 and intervention 2 NMT, and group 3 control. Results: Data analysis using paired tests on ABI in 3 groups showed that in group I the foot exercise intervention resulted in p. 0.001 means there is a change in results before and after the intervention. Likewise, in group II of the NMT intervention, the result was p 0.001, there was a change in results before and after the intervention. Conclusion: Research proves that diabetes foot exercise and NMT interventions can improve ABI values in Type 2 DM patients.